Environmental Health Risk Assessment (EHRA) Of Carbon Monoxide (CO) Exposure Among Fuel Station Operators At Gas Stations In Kota Baru District In 2026 - Muhammad Gusman Syahlun Abyan; Willia Novita Eka Rini; Andree Aulia Rahmat; Oka Lesmana S. (International Journal of Health Engineering and Technology, 2026)
This study aims to analyze environmental health risks caused by carbon monoxide (CO) exposure among gas station operators in Kota Baru District, Jambi City, in 2026 using the Environmental Health Risk Assessment (EHRA) method with a quantitative descriptive approach. The research was conducted from January to February 2026 and involved 61 respondents from five gas stations: SPBU 24.361.70, 24.361.51, 24.361.04, 24.361.13, and 24.361.58. Data collection was carried out through direct measurement of CO concentration using the AS8700A CO meter, wind speed measurement using an anemometer, temperature and humidity measurement using a thermohygrometer, and structured interviews regarding exposure characteristics. The results revealed that two locations showed unsafe risk levels under realtime conditions, namely SPBU 24.361.04 with a Risk Quotient (RQ) value of 1.187 and SPBU 24.361.51 with an RQ value of 1.073, both exceeding the safe threshold (RQ>1). The highest CO concentration was recorded at SPBU 24.361.51, reaching 11.9443 mg/m³. The most dominant health complaints experienced by respondents were fatigue (54.1%) and dizziness (34.4%). Nevertheless, the 30-year lifetime risk projection indicated that all study locations remained within the safe category, with RQ values below 1.